Kebo-Keboan dan Ider Bumi Suku Using: Potret Inklusivisme Islam di Masyarakat Using Banyuwangi - Kholil, Ahmad (el Harakah: Jurnal Budaya Islam, 2011)
This writing presents a discussion on one of cultural heritage in Indonesia which is in the form of magical ceremony having religious nuance. Several aspects of this ceremony, for instance, Animism and Hinduism values are clearly observable, especially in several form and physical orders; on most aspects, however, the aforementioned values trail are obscure as old traditions. Even though the values are considered as old heritage, by polishing and adapting certain creation, the more perceptible value and belief in this ceremony is Islam transcendentalist and humanist. Ider bumi and slametan are the two of cultural heritage having Islamic nuance, while kebo-keboan is an embodiment of Hinduism cultural heritage. In Alasmalang, kebo-keboan ceremony has religious orientation praying to the God for acquiring good harvest, blessed business and achieving wishes. Regarding ider bumi ceremony, which is practiced in most of Using society, is conducted by going around the village while reading kalimah toyyibah and resounding adzan in every side of village. This ceremony’s purpose is to protect the village from any kind of annoyance from human being and devil. Furthermore, socially, kebo-keboan and ider bumi function as harmony keeper among the villagers, nature and with everything in the environment. Tulisan ini membahas salah satu kekayaan budaya bangsa yang menjelma dalam upacara magic bernuansa keagamaan. Pada beberapa sisi masih tampak kental sebagai warisan budaya lama, baik animisme maupun hinduisme, terutama dalam bentuk dan tatanan fisik, tetapi di sebagian besar yang lain sudah tinggal jejak yang samar sebagai warisan lama. Meskipun sebagai warisan leluhur, dengan polesan dan kreasi tertentu, yang tampak sekarang justru nilai dan tradisi Islam yang transendentalis dan humanis. Warisan budaya yang bercita rasa islami itu seperti ider bumi dan slametan, sementara yang masih bernuansa hinduisme adalah kebo-keboan. Kebo-keboan di Alasmalang mempunyai orientasi relijius berupa permohonan kepada Gusti Allah Yang Maha Kuasa agar tanaman, usaha dan tujuan yang hendak diraih mendapat perkenan dan berhasil sesuai harapan. Sementara ider bumi, yang dipraktikkan di sebagian besar masyarakat Using, keliling kampung dengan membaca kalimah thoyyibah dan mengumandangkan adzan di setiap sudut desa adalah bertujuan untuk melindungi desanya dari segala macam gangguan, dari makhluk kasar maupun halus. Di samping kedua tujuan itu, kebo-keboan dan ider bumi ini juga memiliki fungsi sosial, yaitu menjaga kerukunan sosial atau keharmonisan hubungan dengan sesama, alam semesta, dan dengan segala yang ada di lingkungan hidup manusia.